Соціокультурна ідентичність українського п’ятидесятництва - Дмитрук, І. А.; Dmyruk, І. А. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті здійснено спробу проаналізувати соціокультурну ідентичність українського п’ятидесятництва, показати трансформаційні зміни українського п’ятидесятництва за останнє століття. The paper is feasible to analyze socio-cultural identity of Ukrainian Pentecostalism. Adaptation and development of Ukrainian Protestantism had a very complex history of formation and distribution in Ukraine. Beginning in the 16th century. in Ukraine are beginning to penetrate new Christian reform movements. This created a fertile ground for a new wave of Protestantism in the 20 th century already. Active development of Pentecostalism in southern Ukraine has expanded its effects on the entire territory of Ukraine. Having survived the Soviet religious policy Pentecostal leaders have begun to create a culturally identical stratum of society. Thus reflecting its unique identity and membership in a particular religious group.
Socio-cultural identity of Ukrainian Pentecostal Movement
Keywords: п’ятидесятники; Pentecostalism; соціокультурність; Socio-culturalism; українська ідентичність; Ukrainian identity; протестантизм; protestantism; гомілії; homily; харизма; charisma